The effects of learning with various noise on Gait Kinematics in 3-to-5-year-old children: a randomized controlled trial - Maryam Ghorbani; Rasoul Yaali; Wolfgang I. Schöllhorn; Amir Letafatkar; Hassan Sadeghi (BMC, 2022)
Abstract Background Lack of the neuromuscular control during locomotion in the knee joint leads to an increased risk of anterior cruciate ligament (ACL) injury in children. Hence, we aimed to explore the effects of a repetitive, model-oriented, and self-organized approach on lower limb kinematics during gait in children. Methods In randomized controlled trial, 36 children with 4 ± 0.79 years of age from the children gym were randomly (a lottery method) allocated into three groups, including (1) the model-oriented (n = 10), (2) Differential Learning (n = 11), and (3) control (n = 10) groups. Kinematic data of hip, knee, and ankle joints in the sagittal plane were recorded by a GoPro camera at the moments of heel-ground contact and toe-off the ground before and after a 6-week intervention (two sessions per week). Results The results indicate a 35% post-intervention increase of ankle dorsiflexion (95% CI: − 5.63 _ − 0.96) in the moment of heel-ground contact in the model-oriented group; however, knee flexion (95% CI: − 1.05 _ 8.34) and hip flexion (95% CI: 3.01 _ 11.78) were respectively decreased by 20% and 20%. After the intervention, moreover, ankle plantar flexion (95% CI: − 9.18 _ − 2.81) and hip extension (95% CI: − 12.87 _ − 3.72) have respectively increased by 37% and 37%, while knee flexion (95% CI: 3.49 _ 11.30) showed a %16 decrease in the moment of toe off the ground. As for the Differential Learning group, ankle dorsiflexion (95% CI: − 5.19 _ − 1.52) increased by 33%, and knee (95% CI: 0.60 _ 5.76) and hip flexion (95% CI: 2.15 _ 7.85) respectively decreased by 17% and 17% at the moment of the heel-ground contact following the intervention. At toe lifting off the ground, the plantar flexion (95% CI: − 7.77 _ − 2.77) increased by 35%, knee flexion (95% CI: 2.17 _ 7.27) decreased to 14%, and hip extension (95% CI: − 9.98 _ − 4.20) increased by %35 following the intervention for the Differential Learning group subjects. Based on the results obtained from the one-way ANOVA, there was a significant difference between these groups and the control group in all kinematic gait variables (p ≤ 0.05). However, no statistically significant differences were found between the two experimental groups. Conclusions The results implied that the model-oriented repetitive and the self-organized Differential Learning approach were both appropriate to alter the kinematic gait pattern in the 3-5-year-old children. Previous research has almost exclusively recommended a model-oriented approach to change kinematic patterns and preventing non-contact motor injuries. However, the present study showed that the Differential Learning approach can help children to achieve the same goal by continuously changing environments and stimulating challenges. Trial registration: Current Controlled Trials using the IRCT website with ID number of, IRCT20130109012078N5 "Prospectively registered" at 14/5/2021.